2016
DOI: 10.4049/jimmunol.1502178
|View full text |Cite
|
Sign up to set email alerts
|

Allergy-Protective Arabinogalactan Modulates Human Dendritic Cells via C-Type Lectins and Inhibition of NF-κB

Abstract: Arabinogalactan (AG) isolated from dust of a traditional farm prevents disease in murine models of allergy. However, it is unclear whether this polysaccharide has immune regulatory properties in humans. The aim of this study was to test the influence of AG on the immune-stimulating properties of human dendritic cells (DCs). Moreover, we sought to identify the receptor to which AG binds. AG was produced from plant callus tissue under sterile conditions to avoid the influence of pathogen-associated molecular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…The ability of antigen presentation of DCs was assayed in vitro and the results indicated the treatment of immethridine reduced the function of antigen presentation and the inhibitory effect has also been detected in MLR assay. The maturation of DCs could be induced by LPS stimulation via activating NF-κB or MAPK signaling pathway [ 39 , 40 ]. To understand what kind of signaling pathway was involved in the function of immethridine, the signaling pathway of NF-κB and MAPK was analyzed and the results indicated that immethridine could reduce the expression of TLR-4 and CD14, which are receptor or co-receptor of LPS, and down-regulate the phosphorylation of NF-κB p65 but not ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of antigen presentation of DCs was assayed in vitro and the results indicated the treatment of immethridine reduced the function of antigen presentation and the inhibitory effect has also been detected in MLR assay. The maturation of DCs could be induced by LPS stimulation via activating NF-κB or MAPK signaling pathway [ 39 , 40 ]. To understand what kind of signaling pathway was involved in the function of immethridine, the signaling pathway of NF-κB and MAPK was analyzed and the results indicated that immethridine could reduce the expression of TLR-4 and CD14, which are receptor or co-receptor of LPS, and down-regulate the phosphorylation of NF-κB p65 but not ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, DCs have reduced ability to stimulate T lymphocytes. 6 Therefore, it was discussed that inhalation of AG could result in a dampened Th2 cell activation in the lung, thus leading to a reduced allergic sensitization via the airways.…”
Section: A Patent On the Synthesis Of Arabino-oligosaccharides For Rementioning
confidence: 99%
“…7 The AG molecule is large with a molecular mass of 127 kDa. 6 Due to its high mass and structural complexity, the complete chemical synthesis of this molecule is impossible. However, experiments, in which the arabinose side chains were cleaved, suggested that these residues are critically involved in the immune modulatory activity of the molecule.…”
Section: A Patent On the Synthesis Of Arabino-oligosaccharides For Rementioning
confidence: 99%
See 1 more Smart Citation
“… 9 ). Notably, different DC-SIGN ligands are known to induce distinct intracellular signaling pathways and immunological outcomes, supporting an important role for DC-SIGN as a target for immunomodulatory approaches 10 11 12 13 . Finally, thanks to its antigen uptake and signaling properties, DC-SIGN is a promising candidate for the development of vaccines targeting DCs 14 15 .…”
mentioning
confidence: 99%